COVID19 infection in a patient with paroxysmal nocturnal hemoglobinuria: A case report. Issue 20 (21st May 2021) - Sokol, Juraj; Nehaj, Frantisek; Mokan, Michal; Lisa, Lenka; Stasko, Jan
Abstract: Introduction: Paroxysmal nocturnal hemoglobinuria (PNH) is an acquired, life-threatening hemopoietic stem cell disorder characterized by the triad of hemolytic anemia, thrombosis, and impaired bone marrow function. Evidence suggests that severe outcomes in COVID19 infection are attributed to the excessive activation of the complement cascade leading to acute lung injury and associated is with an increased prothrombotic state. Patient concerns: A 27-year-old Caucasian man with PNH presented to the Emergency Department of our hospital with acute onset shortness of breath, cough and blood in urine. Diagnosis: The patient was diagnosed with acute hemolytic exacerbation of PNH complicated with moderate COVID19 pneumonia. Outcomes: The patient was initiated with an anticoagulant unfractionated heparin, dexamethasone, and cefuroxime injection. His symptoms quickly resolved, and he was discharged after 5 days. Conclusion: The complement system activation is a critical component in the sequalae of COVID19 infection. Evidence suggests that severe outcomes in COVID19 infection are attributed to the excessive activation of the complement cascade leading to acute lung injury and associated is with an increased prothrombotic state. Notably, C5a concentration was noted to be higher in patients with COVID19 infection. The use of complement inhibitors to attenuate immune mediated damage in COVID19 nevertheless represents a very interesting theoretical approach. However, careful consideration as to which patients may benefit will be required and the outcome of clinical trials needed.